Implementation of Hierarchy Attribute-Based Encryption (HABE) to Secure Information Stored in Cloud Storage - Arfriandi, Arief; Gernowo, Rahmat; Isnanto, R. Rizal (Universitas Negeri Semarang, 2025)
The usage of cloud storage is currently growing, particularly for media used for information storage. Information saved in cloud storage makes it possible for the owner of the cloud storage to access the Information without the owner's permission. The privacy of access and management of access to the information kept in the cloud storage becomes a problem and security risk when using that cloud storage because the owner cannot ensure that the stored information is only accessed by authorized parties. Access control management is necessary for information owners to guarantee the safety of the information they hold. To regulate access to information kept in cloud storage, this study intends to apply the Hierarchy Attribute-Based Encryption (HABE) technique. A hierarchical attribute base is used to encrypt and decode information saved in cloud storage through the application of HABE, making hierarchical attributes the essential element in controlling access to the information. The hierarchical structure utilized to manage access control for information security will also be detailed in this research. This implementation procedure is completed before the information is stored in cloud storage. The mathematical computations used to secure text information during the encryption and decryption operations are described in the HABE implementation method and debate. By using Hierarchy Attribute-Based Encryption, security concerns with cloud storage can be resolved and flexible access control management in compliance with corporate standards is made possible.